Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw Pada Materi Kesetimbangan Kimia Terhadap Hasil Belajar Siswa Kelas XI MIA SMA Negeri 2 Palu - Sisilia, Maria; Sakung, Jamaluddin; Said, Irwan (Universitas Tadulako, 2015)
The aim of this study is to determine the learning outcomes of students in the class which is treated with the cooperative learning model Jigsaw whether it is better than the untreated class on chemical equilibrium topic. This study is a quasi-experimental research design with Non Randomized Pretest- posttest control group design. The population in this study is 245 students of class XI MIA with academic year 2014/2015, from 8 classes. The sample in this study class XI MIA 5 (n = 32) as an experimental class while class XI MIA 6 (n = 32) as a control class. The analysis of data obtained in the experimental class, X1 1 valueis 79.66 with a standard deviation = 9.41. In the control class, X2 valueis 70.03 with a standard deviation = 11.13. The result of hypothesisis found that tcalculated>ttable (5.53 > 1.67) with a significance level (Î± = 0.05) and degrees of freedom = 62. This shows that H0 is rejected and H1 is accepted. Therefore, it can be concluded that student learning outcomes in class which is treated using the cooperative learning model Jigsaw is better than the untreated class on chemical equilibrium topic.